Change in cervical length and spontaneous preterm birth in nulliparous women with a history of loop electrosurgical excision procedure. (3rd July 2021) - Gupta, Simi; Chen, Stefanie; Naqvi, Mariam; Saltzman, Daniel H.; Rebarber, Andrei; Monteagudo, Ana; Fox, Nathan S.
Abstract: Background: Prior studies have shown an association between history of loop electrode procedures (LEEP) and spontaneous preterm delivery (SPTD) independent of mid-trimester cervical length. These studies suggest that there may be other factors beyond an individual cervical length, which contribute to identifying at-risk pregnancies. Objective: The objective of this study is to determine the association between change in cervical length and SPTD in women with a history of LEEP. Study design: This is a retrospective cohort study of singleton nulliparous women with a history of LEEP who received serial cervical length measurements at a single institution between 2012 and 2016. Women with serial cervical lengths and available outcome data were included. The cervical length at different gestational ages and the rate of change in length were compared with the risk for SPTD <37 weeks using Student's t -test. Results: One-hundred-thirty subjects met the inclusion criteria for the study. The mean cervical length (35.3 versus 39.8 mm, p = .042 at 16 weeks; 32.2 versus 37.8 mm, p < .01 at 20 weeks; 29.9 versus 35.6 mm, p = .027 at 24 weeks; 21.6 versus 33.4 mm, p < .01 at 28 weeks) was significantly different between women who had an SPTD <37 weeks compared to women who did not. The average rate of change in transvaginal cervical length between 16 to 28 weeks was significantly different between women who had an SPTD <37 weeks compared to women who did not (−1.4 versus 0.4 mm/week, p < .01). Conclusion: Women with a history of LEEP who had an SPTD <37 weeks had a shorter cervical length at 16, 20, 24, and 28 weeks' gestation and a higher rate of change in cervical length between 16 and 28 weeks than women without a history of SPTD. Our findings support the concept of the preterm birth syndrome as an evolving biophysical process rather than a distinct event, suggesting improved prediction in the setting of prior history of a LEEP with serial imaging.